Electrophotographic photoreceptor with weakened interference fringes and method for producing the same
Patent Information
- Application Number
- CN202310427453.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-20
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2043-04-20
AI Technical Summary
反射光与写入光产生位相差,进而发生干涉,造成的光强度不均现象,光强度的加强区域和减弱区域均反射至CGL,产生了不同数量的电荷,从而引起电子照相感光体表面电位差异,最终导致画像不均匀
[0027](1)本发明提供了一种弱化干涉条纹的电子照相感光体,通过将三氧化二铁和二氧化钛结合应用于电子照相感光体底涂层,如此,底涂层中的三氧化二铁和二氧化钛构成的混合物,可以改变底涂层的折射率,并增加底涂层对光的吸收,达到弱化照射到导电基体表面的写入光,进而弱化干涉条纹的效果,保证了打印图像的质量,并且与现有技术中添加长条状纳米氧化物的技术方案相比,本发明的技术方案无需使用纳米粒子,进而具有更低的成本优势,因此本发明在低成本下依然获得了一种能够弱化干涉条纹的电子照相感光体。
Smart Images

Figure QLYQS_1 
Figure QLYQS_2 
Figure BDA0004189064970000031
Abstract
Description
Technical Field
[0001] This invention relates to an electrophotographic photosensitive material with weakened interference fringes and its preparation method, belonging to the technical field of electrophotographic imaging elements. Background Technology
[0002] Electrophotographic photosensitive cells (OPCs) are the most crucial components in automated office equipment such as laser printers, laser copiers, and laser multifunction printers, directly affecting the quality of printed and copied images. OPCs are generally manufactured by sequentially coating a conductive substrate (also known as a drum substrate) with an undercoat layer (UCL), a charge generation layer (CGL), and a charge transport layer (CTL).
[0003] The undercoat of an electrophotographic photosensitive image is typically composed of titanium oxide and adhesive resin. During exposure, the write light passes through the undercoat and illuminates the conductive substrate (drum base). Due to the high reflectivity of the drum base, reflected light is generated. The reflected light and the write light have a phase difference, which leads to interference and uneven light intensity. Both areas of increased and decreased light intensity are reflected to the CGL (Conductive Gel Layer), generating different amounts of charge. This causes a difference in surface potential on the electrophotographic photosensitive image, ultimately resulting in an uneven image.
[0004] Currently, there are generally two methods to weaken interference fringes in electrophotographic photosensitive materials: one is to weaken the interference fringes by treating the drum substrate surface, as described in patent application number 200480011809.9. However, this method requires an additional drum substrate treatment step, increases energy consumption, and generates tiny metal particles, which is inconsistent with energy conservation and environmental protection requirements. The other method is to improve the undercoat layer, as described in patent application CN109116691A, which adds elongated nano-oxides to the UCL to weaken the interference fringes of the electrophotographic photosensitive material. However, the elongated nano-oxides added to the undercoat layer are expensive, increasing production costs. Therefore, how to improve the undercoat layer at a lower cost to weaken the interference fringes of electrophotographic photosensitive materials is a technical problem that urgently needs to be solved in this field. Summary of the Invention
[0005] In view of this, the purpose of the present invention is to provide an electrophotographic photosensitive material for weakening interference fringes and a method for preparing the same, wherein the bottom coating of the electrophotographic photosensitive material does not require the addition of nanoparticles and has a good effect on weakening interference fringes.
[0006] To achieve the objectives of this invention, the following technical solutions are provided.
[0007] An electrophotographic photosensitive material for weakening interference fringes, the electrophotographic photosensitive material is composed of a conductive substrate, an undercoat layer (UCL), a charge generation layer (CGL), and a charge transport layer (CTL), and the undercoat layer, the charge generation layer, and the charge transport layer are arranged sequentially from the conductive substrate upwards.
[0008] The base coating is composed of ferric oxide, titanium dioxide, and adhesive resin; the mass ratio of ferric oxide to titanium dioxide is (0.01-1):1; the mass ratio of the sum of the masses of ferric oxide and titanium dioxide to the mass of adhesive resin is (0.1-10):1; the adhesive resin is one or more of phenolic resin, melamine resin, urethane resin, alkyd resin, epoxy resin, nylon resin, polyester resin, polyether resin, and polyvinyl alcohol resin.
[0009] The charge generation layer is composed of a charge generation material and a film-forming resin I in a mass ratio of 1:(0.05~10); the charge generation material and the film-forming resin I are the charge generation materials and film-forming resins conventionally used in charge generation layers in the art;
[0010] The charge transport layer is composed of a charge transport material and a film-forming resin II in a mass ratio of (0.1 to 10):1; the charge transport material and the film-forming resin II are the charge transport materials and film-forming resins conventionally used in charge transport layers in the art.
[0011] The conductive substrate is a conductive substrate conventionally used in the art.
[0012] Preferably, the charge-generating material is an azo pigment, a polycyclic aromatic pigment, a perylene pigment, or a phthalocyanine pigment; the film-forming resin I is one or more of polyvinyl butyral resin, polyarylate resin, polycarbonate resin, polyamide resin, acrylic resin, cellulose resin, epoxy resin, and polyvinyl alcohol resin.
[0013] Preferably, the charge transport material is a triphenylamine compound, which is composed of one or more compounds represented by the following structural formulas (I) to (IX);
[0014]
[0015]
[0016] The film-forming resin II is one or more of the following: polycarbonate resin, polyester resin, polyarylate resin, acrylic resin, polyvinyl chloride resin, polyvinyl acetate resin, silicone resin, silicone alkyd resin, phenol-formaldehyde resin, and polysilane resin.
[0017] Preferably, the charge-generating material is γ-phthalocyanine titanium; the triphenylamine compound is composed of compounds represented by structural formulas (III) and (VII) in a mass ratio of (1-10):1.
[0018] Preferably, the thickness of the base coating is 1.5 μm to 10 μm; the thickness of the charge generation layer is 0.2 μm to 2 μm; and the thickness of the charge transport layer is 10 μm to 50 μm.
[0019] A method for preparing an electron photosensitive material with weakened interference fringes according to the present invention, the steps of which are as follows:
[0020] (1) Preparation of the base coating: After dispersing and mixing ferric oxide, titanium dioxide and solvent I evenly, adhesive resin and solvent I are added, and after dispersing and mixing evenly, a base coating dispersion is obtained. The base coating dispersion is evenly coated onto the surface of the conductive substrate. After drying and removing the added solvent I, a base coating is obtained on the surface of the conductive substrate.
[0021] Solvent I is a solvent commonly used in the preparation of base coatings in this field, and it is one or more of aromatic hydrocarbons, halogenated hydrocarbons, alcohols, ketones, ethers and ester solvents; preferably, solvent I is one or more of methanol, ethanol, isopropanol, n-butanol, acetone, methyl ethyl ketone, cyclohexanone, methyl acetate, ethyl acetate, tetrahydrofuran, dichloromethane, chloroform, chlorobenzene and toluene.
[0022] (2) Preparation of charge generation layer: Disperse and mix the charge generation material, film-forming resin I and solvent II evenly to obtain a charge generation layer dispersion. Coat the charge generation layer dispersion evenly onto the surface of the base coating layer. After drying and removing solvent II, a charge generation layer is obtained on the surface of the base coating layer.
[0023] Solvent II is a solvent commonly used in the preparation of charge-generating layers in the art, and is one or more of halogenated hydrocarbons, ketones, ethers and esters; preferably, solvent II is one or more of dichloromethane, dichloroethane, chlorobenzene, acetone, methyl ethyl ketone, cyclohexanone, tetrahydrofuran, methyl acetate, ethyl acetate and n-butyl acetate; more preferably, solvent II is composed of ethyl acetate, cyclohexanone and methyl ethyl ketone in a mass ratio of 1:(0.01-0.8):(0.01-0.5).
[0024] (3) Preparation of charge transport layer: The charge transport material and film-forming resin II are completely dissolved in solvent III to obtain a charge transport layer solution. The charge transport layer solution is uniformly coated on the surface of the charge generation layer. The added solvent III is dried to remove the charge transport layer on the surface of the charge generation layer, and then the electrophotographic photosensitive material is obtained.
[0025] Solvent III is a solvent commonly used in the preparation of charge transport layers in this field, and is one or more of aromatic hydrocarbons, halogenated hydrocarbons, ketones, and ethers; preferably, solvent III is one or more of chlorobenzene, toluene, benzene, acetone, cyclohexanone, chloroform, dichloroethane, tetrahydrofuran, and diethyl ether. 。
[0026] Beneficial effects
[0027] (1) This invention provides an electrophotographic photosensitive material that weakens interference fringes. By combining ferric oxide and titanium dioxide and applying them to the base layer of the electrophotographic photosensitive material, the mixture of ferric oxide and titanium dioxide in the base layer can change the refractive index of the base layer and increase the absorption of light by the base layer, thereby weakening the writing light irradiating the surface of the conductive substrate and thus weakening the interference fringes. This ensures the quality of the printed image. Compared with the existing technology that adds long strip nano-oxides, the technical solution of this invention does not require the use of nanoparticles, thus having a lower cost advantage. Therefore, this invention still obtains an electrophotographic photosensitive material that can weaken interference fringes at a low cost.
[0028] (2) The present invention provides an electron photosensitive material for weakening interference fringes, which uses triphenylamine compounds as charge transport materials and has the advantages of high charge mobility and good miscibility with resin.
[0029] (3) The present invention provides an electron photosensitive material for weakening interference fringes, which uses γ-phthalocyanine titanium oxide as the charge generating material and has the advantages of good sensitivity and stable dispersion.
[0030] (4) The present invention provides a method for preparing an electrophotographic photosensitive material with weakened interference fringes. Compared with the scheme of processing the surface of the drum substrate to weaken interference fringes, the method has the advantages of not adding new production steps, simple operation, energy saving and environmental protection. Detailed Implementation
[0031] The present invention will be further described below with reference to specific embodiments. Unless otherwise specified, the methods described are conventional methods, and the raw materials described are available from publicly available commercial sources or prepared according to literature.
[0032] Example 1
[0033] An electrophotographic photosensitive material for weakening interference fringes is disclosed. The photosensitive material comprises a conductive substrate, a base coat (UCL), a charge generation layer (CGL), and a charge transport layer (CTL), with the base coat, charge generation layer, and charge transport layer arranged sequentially from the conductive substrate upwards. The fabrication method of the electrophotographic photosensitive material is as follows:
[0034] (1) Preparation of the base coating: By mass, 1 part of ferric oxide, 10 parts of titanium dioxide and 30 parts of methanol are added to a sand mill and dispersed and mixed for 1 hour to achieve a uniform dispersion and mixing state. Then, 22 parts of nylon resin and 50 parts of methanol are added and dispersed and mixed for 3 hours to achieve a uniform dispersion and mixing state, thus obtaining a base coating dispersion. The base coating dispersion is uniformly coated onto the surface of an aluminum-based conductive substrate and placed in an oven to dry at 90°C for 30 minutes, thus obtaining a base coating with a thickness of 2.5 μm on the surface of the aluminum-based conductive substrate.
[0035] (2) Preparation of charge generation layer: 90 parts by mass of γ-phthalocyanine titanium oxide, 50 parts of polyvinyl butyral resin, 2900 parts of ethyl acetate, 450 parts of cyclohexanone and 165 parts of methyl ethyl ketone were added to a sand mill and dispersed and mixed for 10 h to achieve a uniformly dispersed and mixed state, thus obtaining a charge generation layer dispersion. The charge generation layer dispersion was uniformly coated onto the surface of the base coating and placed in an oven to dry at 90 °C for 30 min, thus obtaining a charge generation layer with a thickness of 0.2 μm on the surface of the base coating.
[0036] (3) Preparation of charge transport layer: By mass, 8 parts of the compound represented by structural formula (III), 2 parts of the compound represented by structural formula (VII), 20 parts of polycarbonate resin and 130 parts of tetrahydrofuran were added to a stirred tank and stirred for 21 hours to completely dissolve the compound represented by structural formula (III), the compound represented by structural formula (VII) and the polycarbonate resin in tetrahydrofuran to obtain a charge transport layer solution. The charge transport layer solution was uniformly coated on the surface of the charge generation layer and placed in an oven to dry at 100°C for 50 minutes to obtain a charge transport layer with a thickness of 25 μm on the surface of the charge generation layer, thereby obtaining an electrophotographic photosensitive material.
[0037] The compounds represented by structural formulas (III) and (VII) are as follows:
[0038]
[0039] Example 2
[0040] Unlike Example 1, in step (1) of this example, 3 parts by weight of ferric oxide, 10 parts by weight of titanium dioxide and 30 parts by weight of methanol are added to a sand mill and dispersed and mixed for 1 hour to achieve a uniform dispersion. Then, 26 parts by weight of nylon resin and 50 parts by weight of methanol are added and dispersed and mixed for 3 hours to achieve a uniform dispersion, thus obtaining the base coating dispersion. The rest is the same as in Example 1.
[0041] Example 3
[0042] Unlike Example 1, in step (1) of this example, 3 parts by weight of ferric oxide, 10 parts by weight of titanium dioxide and 30 parts by weight of methanol are added to a sand mill and dispersed and mixed for 1 hour to achieve a uniform dispersion. Then, 3.25 parts by weight of nylon resin and 50 parts by weight of methanol are added and dispersed and mixed for 3 hours to achieve a uniform dispersion, thus obtaining the base coating dispersion. The rest is the same as in Example 1.
[0043] Example 4
[0044] Unlike Example 1, in step (1) of this example, 3 parts by weight of ferric oxide, 10 parts by weight of titanium dioxide, and 30 parts by weight of methanol are added to a sand mill and dispersed and mixed for 1 hour to achieve a uniform dispersion. Then, 3.25 parts by weight of nylon resin and 50 parts by weight of methanol are added and dispersed and mixed for 3 hours to achieve a uniform dispersion, thus obtaining a base coating dispersion. The base coating dispersion is then uniformly coated onto the surface of an aluminum-based conductive substrate and placed in an oven to dry at 90°C for 30 minutes, resulting in a base coating with a thickness of 5 μm on the surface of the aluminum-based conductive substrate. The rest is the same as in Example 1.
[0045] Comparative Example 1
[0046] Unlike Example 1, in step (1) of this comparative example, 10 parts by weight of titanium dioxide and 30 parts by weight of methanol were added to a sand mill and dispersed and mixed for 1 hour to achieve a uniform dispersion. Then, 20 parts by weight of nylon resin and 50 parts by weight of methanol were added and dispersed and mixed for 3 hours to achieve a uniform dispersion, thus obtaining the base coating dispersion. The rest is the same as in Example 1.
[0047] Comparative Example 2
[0048] Unlike Example 1, in step (1) of this comparative example, 10 parts by weight of titanium dioxide and 30 parts by weight of methanol were added to a sand mill and dispersed and mixed for 1 hour to achieve a uniform dispersion. Then, 2.5 parts by weight of nylon resin and 50 parts by weight of methanol were added and dispersed and mixed for 3 hours to achieve a uniform dispersion, thus obtaining the base coating dispersion. The rest is the same as in Example 1.
[0049] Comparative Example 3
[0050] Unlike Example 1, in step (1) of this example, 10 parts by weight of titanium dioxide and 30 parts by weight of methanol are added to a sand mill and dispersed and mixed for 1 hour to achieve a uniform dispersion. Then, 2.5 parts by weight of nylon resin and 50 parts by weight of methanol are added and dispersed and mixed for 3 hours to achieve a uniform dispersion, resulting in a base coating dispersion. The base coating dispersion is then uniformly coated onto the surface of an aluminum-based conductive substrate and placed in an oven to dry at 90°C for 30 minutes, resulting in a base coating with a thickness of 5 μm on the surface of the aluminum-based conductive substrate. The rest is the same as in Example 1.
[0051] Test Example 1
[0052] The electrophotographic photosensitive materials prepared in Examples 1-4 and Comparative Examples 1-3 were printed using a negative electric laser printer. The test results are shown in Table 1.
[0053] Table 1. Printing test results of the electrophotographic photoresists prepared in Examples 1-4 and Comparative Examples 1-3.
[0054]
[0055] Wherein: "×" indicates severe interference fringes; "△" indicates acceptable interference fringes; and "○" indicates no interference fringes. The mass ratio of the metal oxide to the nylon resin is the sum of the masses of ferric oxide and titanium dioxide and the mass ratio of the nylon resin.
[0056] The test results of Example 1 and Comparative Example 1 show that the mass ratio of metal oxide to nylon resin is the same, and the thickness of the base coating is the same. It is precisely because Example 1 contains 1 part by mass of ferric oxide that the electrophotographic photoresist prepared in Example 1 can weaken interference fringes, ensuring print quality and achieving an acceptable level of interference fringes. No interference fringes appeared in the printing results of the electrophotographic photoresist prepared in Examples 2-4, indicating that as the amount of ferric oxide increases, it has a very good weakening effect on interference fringes, achieving a level where the printed image is free of interference fringes.
[0057] Compared to Comparative Example 2, Comparative Example 3 has the same composition of the base coating. The thickness of the base coating in Comparative Example 3 is twice that of Comparative Example 2. Therefore, the test results of Comparative Example 2 show severe interference patterns, while the interference patterns in Comparative Example 3 are acceptable. However, compared to Example 1, although the thickness of the base coating in Comparative Example 3 is higher than that in Example 1, Example 1 contains ferric oxide. Therefore, even though the mass ratio of metal oxide to nylon resin in Example 1 is less than that in Comparative Example 3, the interference patterns in its test results are still acceptable.
[0058] In summary, by combining ferric oxide and titanium dioxide in the base coating of an electrophotographic photosensitive material, it is possible to reduce the preparation cost of the base coating while weakening the writing light irradiating the conductive substrate surface, thereby reducing interference fringes.
[0059] This invention includes, but is not limited to, the above embodiments. Any equivalent substitutions or partial improvements made under the spirit and principles of this invention shall be considered within the scope of protection of this invention.
Claims
1. An electrophotographic photosensitive material for weakening interference fringes, characterized in that: The electrophotographic photosensitive material consists of a base coating layer, a charge generation layer, and a charge transport layer, arranged sequentially from the conductive substrate upwards. The base coating is composed of ferric oxide, titanium dioxide, and adhesive resin; the mass ratio of ferric oxide to titanium dioxide is (0.1~0.3):1; the mass ratio of the sum of the masses of ferric oxide and titanium dioxide to the mass of adhesive resin is (0.5~4):1; the adhesive resin is nylon resin. The charge generation layer is composed of charge generation material and film-forming resin I in a mass ratio of 9:5; The charge transport layer is composed of charge transport material and film-forming resin II in a mass ratio of 1:2; The charge-generating material is γ-phthalocyanine titanium oxide; The film-forming resin I is polyvinyl butyral resin; The charge transport material is a triphenylamine compound composed of compounds represented by structural formulas (III) and (VII) in a mass ratio of 4:1; The film-forming resin II is a polycarbonate resin; , 。 2. An electrophotographic photosensitive material for weakening interference fringes according to any one of claims 1, characterized in that: The thickness of the base coating is 1.5μm to 10μm; the thickness of the charge generation layer is 0.2μm to 2μm; and the thickness of the charge transport layer is 10μm to 50μm.
3. A method for preparing an electron photographic photoreceptor with weakened interference fringes as described in claim 1 or 2, characterized in that: The method steps are as follows: (1) Disperse and mix ferric oxide, titanium dioxide and solvent I evenly, then add adhesive resin and solvent I, disperse and mix evenly to obtain a base coating dispersion, uniformly coat the base coating dispersion onto the surface of the conductive substrate, and obtain a base coating on the surface of the conductive substrate after drying; the solvent I is one or more of aromatic hydrocarbons, halogenated hydrocarbons, alcohols, ketones, ethers and ester solvents; (2) Disperse and mix the charge generating material, film-forming resin I and solvent II evenly to obtain a charge generating layer dispersion. Coat the charge generating layer dispersion evenly onto the surface of the base coating layer. After drying, a charge generating layer is obtained on the surface of the base coating layer. Solvent II is one or more of halogenated hydrocarbons, ketones, ethers and ester solvents. (3) The charge transport material and film-forming resin II are completely dissolved in solvent III to obtain a charge transport layer solution. The charge transport layer solution is uniformly coated on the surface of the charge generation layer. After drying, a charge transport layer is obtained on the surface of the charge generation layer, thereby obtaining the electron photographic photosensitive material. The solvent III is one or more of aromatic hydrocarbons, halogenated hydrocarbons, ketones and ethers.
4. The method for preparing an electron photographic photoreceptor with weakened interference fringes according to claim 3, characterized in that: Solvent I is one or more selected from methanol, ethanol, isopropanol, n-butanol, acetone, methyl ethyl ketone, cyclohexanone, methyl acetate, ethyl acetate, tetrahydrofuran, dichloromethane, chloroform, chlorobenzene, and toluene; Solvent II is one or more selected from dichloromethane, dichloroethane, chlorobenzene, acetone, methyl ethyl ketone, cyclohexanone, tetrahydrofuran, methyl acetate, ethyl acetate, and n-butyl acetate; Solvent III is one or more of chlorobenzene, toluene, benzene, acetone, cyclohexanone, chloroform, dichloroethane, tetrahydrofuran, and diethyl ether.
5. The method for preparing an electron photographic photoreceptor with weakened interference fringes according to claim 4, characterized in that: Solvent II is composed of ethyl acetate, cyclohexanone, and methyl ethyl ketone in a mass ratio of 1: (0.01~0.8): (0.01~0.5).
Citation Information
Patent Citations
Substrate for electrophotographic photoreceptor, process for producing the substrate, and electrophotographic photoreceptor employing the substrate
CN1781059A
A formula for weakening the influence of a substrate surface on the characteristics of an organic photosensitive drum
CN109116691A
Method for preparing electrophotographic photoreceptor
KR1020070120751A